Environmental Assessment of the Water of Haditha Dam and Reservoir for the Period (2023–2024) Using the Canadian Water Quality Index (CCME-WQI) - Rajaa Kadhim Mutar ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
The study addressed an environmental assessment of the water of Haditha Dam and lake for the period (2023–2024), located at the geographical coordinates 34°12'26"N – 42°21'17"E. The Canadian Water Quality Index (CCME WQI) for drinking water fluctuated: in 2023, the water at the lake’s sampling site and the river’s tail-end site during the combined winter and autumn seasons fell within guideline category II and was classified as Good, whereas during the combined spring and summer seasons it was classified as Fair. In contrast, the water quality for irrigation, livestock consumption, and construction purposes fell within guideline category I Excellent. For drinking-water samples in 2024, summer-season water fell within the Excellent category, whereas the river sample at the dam’s tail-end fell within guideline category II. During winter and spring, the lake and river waters together were within guideline category II, while autumn water quality fell within guideline category III Fair. For all seasons of 2024, the water was classified as Excellent for livestock consumption and for construction uses, and Good (guideline category II) for irrigation purposes.DOI: https://doi.org/10.54633/2333-025-058-010